Mechanical behavior of concrete filled glass fiber reinforced polymer-steel tube under cyclic loading - Zhu, Chun-yang; Zhao, Ying-hua; Gao, Shuang; Li, Xiao-fei (Journal of Zhejiang University. A. Science, 2013)
The mechanical behavior of concrete-filled glass fiber reinforced polymer （GFRP）-steel tube structures under com- bined seismic loading is investigated in this study. Four same-sized specimens with different GFRP layout modes were tested by a quasi-static test system. Finite element analysis （FEA） was also undertaken and the results were presented. Results of the nu- merical simulation compared well with those from experimental tests. Parametric analysis was conducted by using the FE models to evaluate the effects of GFRP thickness, axial compression rate, and cross sectional steel ratio. The experimental and numerical results show that the technique of GFRP strengthening is effective in improving the seismic performance of traditional concrete-filled steel tubes, with variations related to different GFRP layout modes.